2018
DOI: 10.1002/casp.2358
|View full text |Cite
|
Sign up to set email alerts
|

Managing stake and accountability in Prime Ministers' accounts of the “refugee crisis”: A longitudinal analysis

Abstract: Taking a (critical) discursive psychological approach, the present study explores the identity management of the Finnish and Swedish Prime Ministers (PM) in relation to the “refugee crisis” and their countries' asylum policies. By taking a longitudinal approach and analysing the PMs' accounts of the “refugee crisis” from 1‐year period, we focused on the ways rhetorical devices related to ethos, logos, and pathos were used to manage the issues of stake and accountability, as well as on the ways in which categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…This research also suggested that the news coverage shifted from European to national issues in late August 2015, when an increasing number of asylum seekers arrived in Finland, and the discourse on restricting their numbers intensified (Pantti 2016;Vij 2016). The same rhetorical shift was found in a longitudinal analysis of Finnish Prime Minister's accounts of the refugee crisis over a 1-year period, which shifted from a discourse of pathos and ethos to a discourse of logos and homogenization, emphasizing rationality to justify tightened immigration policies (Sakki and Pettersson 2018). In order to cover the entire period of the refugee crisis in Finland, this study focuses on the 2-year period from January 2015 until December 2016.…”
Section: Context Of the Study: Finlandmentioning
confidence: 77%
“…This research also suggested that the news coverage shifted from European to national issues in late August 2015, when an increasing number of asylum seekers arrived in Finland, and the discourse on restricting their numbers intensified (Pantti 2016;Vij 2016). The same rhetorical shift was found in a longitudinal analysis of Finnish Prime Minister's accounts of the refugee crisis over a 1-year period, which shifted from a discourse of pathos and ethos to a discourse of logos and homogenization, emphasizing rationality to justify tightened immigration policies (Sakki and Pettersson 2018). In order to cover the entire period of the refugee crisis in Finland, this study focuses on the 2-year period from January 2015 until December 2016.…”
Section: Context Of the Study: Finlandmentioning
confidence: 77%
“…Previous studies on anti-immigration political discourses have shown that they use subtle discursive constructions of otherness (Sakki and Pettersson, 2016) – as well as accusations of racism (Durrheim et al, 2018) – to appeal to their supporters. Previous research has also demonstrated the mainstreaming of the rhetoric of these movements among the political elite (Sakki and Pettersson, 2018; Wodak, 2015). By examining the ways in which anti-immigration political rhetoric was normalised and rendered as appealing through framing Immonen’s act as normal political conduct, this study increases understandings of how anti-immigration discourse is circulated in the lay discourse.…”
Section: Concluding Discussionmentioning
confidence: 97%
“…Horsti and Nikunen, 2013). As a result, anti-immigration voices have become more mainstream in the Finnish public discourse (Pyrhönen, 2015; Sakki and Pettersson, 2018) and attitudes towards immigration have become more polarised among the political elite (Lönnqvist et al, 2019). Thus, while anti-immigration voices have become more salient and accepted in public discourse, they are also increasingly challenged.…”
Section: The Societal Context Of the Studymentioning
confidence: 99%
“…A content analysis based on the same media data that I apply in a qualitative manner, finds that Danish print media more often mention negative consequences of immigration. Swedish media are more positive, while Norwegian media occupies a position in-between on such a positive-negative continuum (Hovden, Mjelde, & Gripsrud, 2018; see also Greussing & Boomgaarden, 2017;Sakki & Pettersson, 2018). Interestingly, the study also compares Scandinavian broadsheets to broadsheets in France, Germany and the UK, and finds that coverage in all the Scandinavian countries appears to be less problem orientated than in the other countries.…”
Section: Immigration Politics and Refugees' Social Rights In Scandinaviamentioning
confidence: 87%